Gap phase regeneration of tree species of differing successional status in a humid tropical forest of Kerala, India - U I CHANDRASHEKARA and S RAMAKRISHNAN (J. Biosci., Vol. 18, Number, June 1993, pp 279-290., 1993)
Germination, establishment and growth of seedlings of tree species Palaquium ellipticum (primary), Actinodaphne malabarica (late secondary) and Macaranga peltata (early secondary) were studied in a humid tropical forest at Nelliampathy, in the Western Ghats of Kerala. While the primary species completed its germination within a brief period of 15 months, at the other extreme, early secondary species showed slow germination extending for about 5 months, the late secondary species falling in between. Although, all the species studied showed higher establishment and growth under gaps, the early secondary species were more responsive compared to the primary species. Primary species showed better establishment in undisturbed sites and natural gaps than under selection felled gaps; the reverse was true for late and early secondary species. Survival of seedlings increased with gap size, but sharply declined with gap age. Shoot/root ratio was consistently higher in the early secondary species than in the primary species.